2022
DOI: 10.1128/spectrum.00700-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequencing of Bacillus cereus Sensu Lato Strains Isolated from Meat and Poultry Products in South Africa Enables Inter- and Intranational Surveillance and Source Tracking

Abstract: Nationwide foodborne pathogen surveillance programs that use high-resolution genomic methods have been shown to provide vast public health and economic benefits. However, Bacillus cereus sensu lato is often overlooked during large-scale routine WGS efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Several extensively analyzed strains have been derived from diverse sources, such as fermented foods [ 62 ], meat and poultry products [ 63 ], and plants [ 64 ]. Investigations utilizing whole-genome sequencing techniques have unveiled strains of B. paranthracis exhibiting potential probiotic characteristics [ 64 ] and demonstrating biodegradation capabilities [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several extensively analyzed strains have been derived from diverse sources, such as fermented foods [ 62 ], meat and poultry products [ 63 ], and plants [ 64 ]. Investigations utilizing whole-genome sequencing techniques have unveiled strains of B. paranthracis exhibiting potential probiotic characteristics [ 64 ] and demonstrating biodegradation capabilities [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…and collaborators isolated B. cereus group strains during routine surveillance of meat products ( 12 ). WGS was conducted on some strains ( 13 ). I.M.…”
Section: The Studymentioning
confidence: 99%
“…and L.M.C. assigned B. cereus group strains to species using multiple WGS-based methods ( 13 ); one method relied on the Genome Taxonomy Database (GTDB), a popular contemporary microbial species classification framework ( 14 ). GTDB releases R95 and R202 classified 2 strains as B. anthracis ( Table 1 ); however, neither strain belonged to the historical, clonal B. anthracis lineage ( 6 ), and neither possessed anthrax toxin- or capsule-encoding genes ( Table 1 ; Figure 1 ).…”
Section: The Studymentioning
confidence: 99%
“…A previous study indicated that some whole genome sequencing (WGS)-based species classification methods pertaining to the B. cereus group can be easily misinterpreted [ 2 ]. Current species definitions of the B. cereus group result in overlapping genomospecies clusters, with 66.2% of genomes belonging to multiple genomospecies at a conventional 95 average nucleotide identity (ANI) threshold, while a ≈92.5 ANI threshold reveals distinct genomospecies clusters with minimal overlap [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus paranthracis , first identified in 2017, was historically referred to as B. cereus or group III B. cereus and encompasses B. cereus group strains capable of causing emetic and/or diarrhoeal foodborne illness [ 3 ]. Here, we conducted a retrospective study on a water-borne outbreak caused by B. paranthracis and the contamination status of paranthracis in the surrounding water systems.…”
Section: Introductionmentioning
confidence: 99%